2016
DOI: 10.14419/ijbas.v5i1.5614
|View full text |Cite
|
Sign up to set email alerts
|

Variations in yield and composition of leaf essential oil from Syzygium aromaticum at various phases of development

Abstract: The changes in the essential oil yield and composition from Syzygium aromaticum leaf harvested at different phases of development from young leaves to mature leaves were studied. Separation of the essential oils was conducted by steam distillation in a Clevenger apparatus for about 4h. Essential oils analyses were performed by GC/MS. The yield of essential oil (ml per 100 g of DM) of the leaf following the four phases of development was in order of: young leaves (5.1%) > expanded leaves 1 (4.5%) > expanded lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…According to the research on Syzygium aromaticum, a considerable proportion of essential oil is collected in the juvenile stages of leaves, with the largest output being in young leaves (5.1%), followed by expanded leaves (4.5%), expanded leaves (4.1%), and the mature leaves (3.8%) [22]. Previous research has found a link between canopy structure, sunshine exposure, and the resulting plant bioactive compounds [23].…”
Section: Volatile Compounds Of Immature and Mature B Balsamifera Leaf...mentioning
confidence: 99%
“…According to the research on Syzygium aromaticum, a considerable proportion of essential oil is collected in the juvenile stages of leaves, with the largest output being in young leaves (5.1%), followed by expanded leaves (4.5%), expanded leaves (4.1%), and the mature leaves (3.8%) [22]. Previous research has found a link between canopy structure, sunshine exposure, and the resulting plant bioactive compounds [23].…”
Section: Volatile Compounds Of Immature and Mature B Balsamifera Leaf...mentioning
confidence: 99%